2019
DOI: 10.1152/ajpheart.00550.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation measurement using rapid changes in head positioning: experiences in acute ischemic stroke and healthy control populations

Abstract: The ideal technique for dynamic cerebral autoregulation (dCA) assessment in critically ill patients should provide considerable variability in blood pressure (BP) but without the need for patient cooperation. We proposed using rapid head positioning (RHP) over spontaneous BP fluctuations for dCA assessment in patients with acute ischemic stroke (AIS). Cerebral blood velocity (transcranial Doppler), beat-to-beat BP (Finometer), and end-tidal CO2 (capnography) were recorded during 5-min baseline and RHP in 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 59 publications
(66 reference statements)
2
32
0
1
Order By: Relevance
“…This could be explained by an improvement in peri-infarct tissue from visit 1 to visit 2. A study also demonstrated the concept of improvement, where in response to rapid head positioning in visit 2 (~7 days) improved CBFV was observed [28]. However, in both this study and Lam et al (2019), visit 3 seemed to associate with loss of this initial improvement, and subsequently stroke symptoms worsened [28].…”
Section: Ais Patientssupporting
confidence: 52%
See 2 more Smart Citations
“…This could be explained by an improvement in peri-infarct tissue from visit 1 to visit 2. A study also demonstrated the concept of improvement, where in response to rapid head positioning in visit 2 (~7 days) improved CBFV was observed [28]. However, in both this study and Lam et al (2019), visit 3 seemed to associate with loss of this initial improvement, and subsequently stroke symptoms worsened [28].…”
Section: Ais Patientssupporting
confidence: 52%
“…A study also demonstrated the concept of improvement, where in response to rapid head positioning in visit 2 (~7 days) improved CBFV was observed [28]. However, in both this study and Lam et al (2019), visit 3 seemed to associate with loss of this initial improvement, and subsequently stroke symptoms worsened [28]. In contrast, other studies observed impaired CA in the sub-acute phase before recovery in the following weeks [36,37].…”
Section: Ais Patientssupporting
confidence: 48%
See 1 more Smart Citation
“…Stroke severity was reported using the National Institutes of Health Stroke Scale (NIHSS) in 13 studies. 16,2031 Mean NIHSS range was 3–19. Lesion side was reported in 14 studies, 15,20,2326,2830,3236 while only 4 reported thrombolytic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies ( n = 243), participants were assessed within 24 h of stroke onset. 16,2022,25,30,31 In four studies ( n = 80), they were assessed within 48 h, 16,28,29,37 while in seven studies ( n = 136), it was within seven days. 15,21,23,24,31,36,38 In the final seven studies ( n = 142), patients were assessed over seven days; 26,27,3135 months 3234 or years 26,35 post-stroke (16 days to 6 years, Table 1).…”
Section: Resultsmentioning
confidence: 99%